THE PREVALENCE OF CHILDHOOD OBESITY IN PUBLIC VERSUS PRIVATE SCHOOLS IN ROMANIA - A COMPARATIVE STUDY (University Arena, 2025)
Childhood obesity is an alarming public health issue in many countries worldwide, with over 41 million overweight children under the age of five, according to WHO (1). In 2013, in Romania, 26.75% of 8-years old children have been diagnosed as overweight and 11.64% as obese, according to Romanian National Institute of Public Health (2).Study Objective & Methods. Considering these data, the aim of the current investigation was to study whether the type of school (public or private) has an impact on childhood obesity. For this purpose, we analysed the Body Mass Index (BMI) of 209 children from four different Romanian schools (three public schools and one private school). The BMI is a body weight measure based on the mass and the height of an individual.Results. Our results indicate that the children from public school have an increased tendency towards obesity compared to children who attend a private school. The main factors identified to contribute to these differences are diet, schedule overload and the personal preference towards organized physical activities. Specifically, children from the public school have a more disorganized eating program, a high-carbohydrate diet and a lower preference towards organized physical activities whereas the children attending the private school have a more balanced dietary program and a higher preference towards organized physical activities.Conclusions. From this study we conclude that more refined national guidelines concerning diet and physical activities for children from both public and private schooled children would have beneficial long and short terms effect.
Keywords: childhood obesity; public vs private school; diet; physical activity